2016
DOI: 10.6002/ect.2014.0163
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Restless legs syndrome is a disorder in which patients have irresistible urge to move legs during rest. Restless legs syndrome seems to be common in end-stage renal disease. After a successful renal transplant, symptoms ameliorate with renal function improvement and restless legs syndrome is seen less in this population. Here, we aimed to investigate restless legs syndrome frequency and associated factors in renal transplant patients. Materials and Methods:In a cross-sectional study with 193 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, another previous study revealed no such relationships (Kim et al, 2008). A recent cross-sectional study between control group, renal transplantation group and hemodialysis group found that prevalence in renal transplantation is significantly lower than in hemodialysis patients (Kahvecioglu et al, 2016). RLS is very prevalent in end-stage renal disease patients, and hemodialysis patients with RLS were found to have a higher risk of muscle atrophy (Giannaki et al, 2011), cardio/cerebrovascular events and mortality (Lin C.H.…”
Section: Secondary Rlsmentioning
confidence: 99%
“…However, another previous study revealed no such relationships (Kim et al, 2008). A recent cross-sectional study between control group, renal transplantation group and hemodialysis group found that prevalence in renal transplantation is significantly lower than in hemodialysis patients (Kahvecioglu et al, 2016). RLS is very prevalent in end-stage renal disease patients, and hemodialysis patients with RLS were found to have a higher risk of muscle atrophy (Giannaki et al, 2011), cardio/cerebrovascular events and mortality (Lin C.H.…”
Section: Secondary Rlsmentioning
confidence: 99%
“…One of them, as mentioned earlier, is the timing of HD sessions, showing that evening dialysis is associated with improved sleep quality compared to daytime dialysis [14]. Additionally, kidney transplantation has been found to significantly reduce the prevalence of insomnia among patients with ESRD [23].…”
Section: Insomniamentioning
confidence: 94%
“…In addition to the adjustments made to the KRT regimen, another treatment option that addresses both kidney failure and related sleep apnea in patients with ESRD is kidney transplantation. A recent crosssectional study suggested significant improvement in sleep apnea following successful kidney transplantation [23]. By recognizing the complex association between kidney disease and sleep apnea, healthcare providers can personalize interventions to address the specific needs of ESRD patients, leading to improved management and care outcomes.…”
Section: Sleep Apneamentioning
confidence: 99%
“…Mohammadi et al performed a single-blind, randomized controlled trial, and he found that near-infrared light can decrease symptoms of RLS in hemodialysis patients [37]. Kahvecioglu et al declared that there is an improvement of RLS in hemodialysis patients after renal transplantation and normalization of the kidney functions [38]. In a clinical trial conducted by Nasiri et al to assess the effect of massage with olive oil after dialysis sessions on RLS patients, the study stated that olive oil can be used as a complementary treatment for RLS since it improves the symptoms significantly [39].…”
Section: Non-pharmacologic Treatmentmentioning
confidence: 99%